2021
DOI: 10.3390/ijms222413345
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ATRA, Natural Ligand of Retinoic Acid Receptors, on EMT-Related Proteins in Breast Cancer: Minireview

Abstract: The knowledge of the structure, function, and abundance of specific proteins related to the EMT process is essential for developing effective diagnostic approaches to cancer with the perspective of diagnosis and therapy of malignancies. The success of all-trans retinoic acid (ATRA) differentiation therapy in acute promyelocytic leukemia has stimulated studies in the treatment of other tumors with ATRA. This review will discuss the impact of ATRA use, emphasizing epithelial-mesenchymal transition (EMT) proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…ATRA is now widely used in preclinical and clinical studies and has shown great anticancer potential in phase II and III clinical trials in patients with various cancers [180]. Specifically, ATRA has been shown to reverse the EMT process in breast cancer cells and hepatocarcinoma cells [195][196][197]. Compared with the prevention of EMT induction, a promising alternative strategy is to selectively target EMT-induced mesenchymal-like cancer cells by therapeutically inhibiting the functions of EMT-specific markers.…”
Section: Other Emt-targeted Therapies In Clinical Applicationsmentioning
confidence: 99%
“…ATRA is now widely used in preclinical and clinical studies and has shown great anticancer potential in phase II and III clinical trials in patients with various cancers [180]. Specifically, ATRA has been shown to reverse the EMT process in breast cancer cells and hepatocarcinoma cells [195][196][197]. Compared with the prevention of EMT induction, a promising alternative strategy is to selectively target EMT-induced mesenchymal-like cancer cells by therapeutically inhibiting the functions of EMT-specific markers.…”
Section: Other Emt-targeted Therapies In Clinical Applicationsmentioning
confidence: 99%
“…Subsequently, ATRA has also been used in the treatment of central nervous system disorders (depression), allergic disorders (asthma), metabolic disorders (atherosclerosis), infectious disorders (invasive pulmonary aspergillosis and bacterial infections), tumor immunity and other diseases ( Sakamoto et al, 2015 ; Hu et al, 2020 ; Campione et al, 2021 ; Kalisz et al, 2021 ; Ma et al, 2022 ). In solid tumors, ATRA promotes programmed death ligand-1 (PD-L1) expression to modulate immunosurveillance in gastric cancer (GC), ATRA treats breast cancer by reversing the mesenchymal transcription programs, and disruption of ATRA signaling plays a role in driving aberrant behavior in cancer stem cells ( Bobal et al, 2021 ; Ma et al, 2022 ; Brown, 2023 ). ATRA is not new to hematologists.…”
Section: Introductionmentioning
confidence: 99%